Architecture Image of Baghdad City during the Mamluk Rule As Seen by Foreign Travelers - Al-Salih, Parizat i Qassim (Iraqi Journal of Architecture and Planning, 2018)
The Mamluks rule of Baghdad (1749-1831 AD) is considered an important stage in the history of Iraq being an introductory stage in the modern Iraq history. The research identified its cognitive problem as follows: the lack of Knowledge about the important elements or components of Baghdad city image and its characteristics, both on urban and architectural level, which draw the attention or concentration of the most prominent foreign travellers, each separately, when they visited the city during the Mamluk rule, so they mentioned and described these subjects in their accounts about the journey. First. Moreover there is no clear and somewhat comprehensive architectural image of Baghdad during the Mamluk rule which depends in its drawing only on those travellers’ accounts and describes the elements and components which form the city and its characteristics. Thus the research aims to: draw an architecture image of Baghdad city specific to each traveller selected. First. Then draw a clear and somewhat comprehensive architectural Image for the city of Baghdad, on both urban and architectural levels, during the Mamluk rule by collecting the previous specific images in one comprehensive image. Second. The research has established a general theoretical framework for drawing the architectural image of any city and then applied it using the accounts of four most prominent Europeans travellers, thus the objectives of the research have been achieved. Finally, the main research conclusions were put forward. Key Words: Image, Architecture Image, Foreign Travelers, Mamluks, Architectural Elements, Urban Component